2021
DOI: 10.1038/s41598-021-87395-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of razor clam Sinonovacula constricta in Ariake Bay, Japan, revealed using RAD-Seq SNP markers

Abstract: The razor clam Sinonovacula constricta is a commercially important bivalve in Japan. The current distribution of this species in Japan is limited to Ariake Bay, where the fishery stock is declining. It is necessary to understand the genetic population structure of this species in order to restore the fishery stock while preserving the genetic diversity of the clam. Here, we report for the first time the genetic population structure of S. constricta in Ariake Bay, Japan. Paired-end restriction site-associated D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Therefore, we suggested that broodstock should be selected according to the mating system and reproductive success of black sea bream in order to avoid biased reproductive contribution. Expanding the number of native breeders and collecting fertilized eggs at several times could also help in decreasing the genetic differences and conserving a larger genetic resource of natural populations [54,55]. Moreover, substantial loss of genetic variation can happen after just one generation [56].…”
Section: Genetic Evaluation Of the Stock Enhancementmentioning
confidence: 99%
“…Therefore, we suggested that broodstock should be selected according to the mating system and reproductive success of black sea bream in order to avoid biased reproductive contribution. Expanding the number of native breeders and collecting fertilized eggs at several times could also help in decreasing the genetic differences and conserving a larger genetic resource of natural populations [54,55]. Moreover, substantial loss of genetic variation can happen after just one generation [56].…”
Section: Genetic Evaluation Of the Stock Enhancementmentioning
confidence: 99%
“…In contrast, population genetic work conducted on related pharids, including Chinese razor clams ( Sinonovacula constricta ) along the coasts of China and Japan (Guo et al 1999, Niu et al 2012, Orita 2021) and the pod razor shell ( Ensis siliqua ) in European coastal waters (Fernández-Tajes et al 2007, Varela et al 2012), do not describe consistent patterns of structuring, except perhaps on broader spatial scales (1,000 s of km). Instead, gene flow appears to be regionally specific and dependent on myriad factors like hydrographic processes, habitat availability, anthropogenic influences, or other unidentified mechanisms.…”
Section: Introductionmentioning
confidence: 98%
“…This method has great advantages in the number of SNPs acquired and the ability to identify novel SNPs compared with SNP chip technology. Restriction site-associated DNA sequencing (RAD-seq) is one of the RRS technologies, which can be used to survey a host of unlinked genetic markers adjacent to restriction sites [ 12 , 13 ] and applied to the research of the gene flow [ 14 , 15 , 16 ], phylogenetic research [ 17 ], and mapping genes of important traits [ 10 , 12 , 18 , 19 , 20 ]. In particular, RAD-seq technology is widely used in some domestic animals, including chickens [ 21 , 22 ] and pigs [ 23 ].…”
Section: Introductionmentioning
confidence: 99%